Antiskin Cancer and Antioxidant Activities of Formulated Agar from Brown Seaweed Laminaria digitata (Hudson) in Dimethyl Benzanthracene-Induced Swiss Albino Mice - Jeneesha George; A. Thabitha; N. Vignesh; V. Manigandan; R. Saravanan; Ghaji Daradkeh; M. Walid Qoronfleh (International Journal of Polymer Science)
This study explores the antiskin cancer effect of formulated agar (FA) from Laminaria digitata on dimethyl benzanthracene- (DMBA-) induced skin cancer mice. The agar was extracted and formulated (emulgel), and FA was biochemically characterized. The in vitro cytotoxicity of FA was tested using NTT 3T3 mice fibroblast cells. The mice were divided into 5 groups: group 1 served as control mice, group 2 mice were considered as DMBA-induced cancer control, group 3 mice were FA pretreated (low dose) + DMBA-induced mice, group 4 mice were FA pretreated (high dose) + DMBA-induced mice, and group 5 were positive control + DMBA-induced mice. The behaviour and biochemical markers of cancer were significantly decreased in group 2 (DMBA-induced) mice, which were brought to near normalcy by FA pretreated mice (groups 3 and 4). The levels of p53 and keratin were significantly elevated in group 2 mice and these levels were decreased in 3 and 4 mice as well. The histopathological examination of DMBA-induced mice was shown degenerated cervical patches in the skin, cirrhosis in liver, oedema in the renal tissue, and swollen and damage in cardiac tissue, which were reduced for the mice applied with FA. This confirms that FA pretreatment offered potential antiskin cancer property.